The planning guide to piping design - Beale, Richard, 1955- (Gulf Pub., 2010)
Peter Smith has joined forces with skilled consultants to take his piping series to the next level. The Planning Guide to Piping Design covers the entire process of planning a plant model project from conceptual to mechanical completion, and explains where the piping lead falls in the process along with his roles and responsibilities. Piping Engineering Leads (or PEL's) used to only receive on-the-job training to learn the operation of producing a process plant. Over time, more schools and programs have developed a more advanced curriculum for piping engineers and designers. However, younger generations of engineers and designers are growing up with a much more technological view of piping design and are in need of a handbook that will explain the proven methods of planning and monitoring the piping design in step-by-step processes. This handbook will provide mentors in the process piping industries the bridge needed for the upcoming engineer and designer to grasp the requirements of piping supervision in the modern age.